Numerical Simulation of the CS2-Filled Active Fiber With Flattened All-Normal Dispersion - ChunCan Wang; CaiPing Jia; JianFang Yang; MuGuang Wang; JingJing Zheng; Li Pei (IEEE Photonics Journal, 2021)
A CS2-filled Er-doped fiber, which can provide high nonlinearity and gain, low and flat all-normal dispersion profile, low loss and single-mode operation in the wavelength range of 1500–2500 nm, is proposed and analyzed by numerical simulation. When the 1900-nm 0.1-ps initial pulse with a peak power of 30 kW is injected into the active fiber, the generated supercontinuum (SC) spectrum has a double-hump structure in the 1550-nm window and covers about 800-nm wavelength range spanning from 1400 to 2200 nm at −20 dB level. Furthermore, the 1550-nm pulse can be obtained synchronously with the 1900-nm initial pulse when the amplified pulse with a temporal double-peak shape is passed through a band-pass filter with its center wavelength at 1550 nm.